2022
DOI: 10.24940/ijird/2022/v11/i3/mar22031
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress on Employee Performance: The Case of African Methodist Episcopal Zion Hospital in the Offinso North District of Ghana

Abstract: The study sought to identify the conditions and factors that generate acute stress among the workers in the public service with particular emphasis on workers at A.M.E Zion Hospital in the Offinso North District and the extent to which it impacts on effective service delivery and performance. The in-depth semi-structured interviews were employed to obtain data. To this end, a case study methodology design was used. In all, 25 health workers were interviewed at the hospital facility, 5 at the Ante Natal Center,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Team Effort Boakye (2015) found that teamwork is positively associated with organizational performance and has significant impact on organizational performance. In another study, Manzoor et al (2011) highlighted that the positive and significant relationship exist between teamwork and employees' performance.…”
Section: Job Aidsmentioning
confidence: 99%
“…Team Effort Boakye (2015) found that teamwork is positively associated with organizational performance and has significant impact on organizational performance. In another study, Manzoor et al (2011) highlighted that the positive and significant relationship exist between teamwork and employees' performance.…”
Section: Job Aidsmentioning
confidence: 99%
“…Studies have shown that public sector employees (PSE) work under pressure, are overworked, and spend much time working tediously, neglecting their health 10,11 . In Ghana, most PSE are expose to stress workload, role ambiguity, role insufficiency, work family relations, adverse working conditions, career development, time pressure, individual factors, organizational adjustment, changing global scene, and working under two perceived supervisors 12,13 . The nature of the work of PSE is such that they may not even have spare time to eat well, engage in physical activities, or even go for regular medical checkups 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In Ghana, most PSE are expose to stress workload, role ambiguity, role insufficiency, work family relations, adverse working conditions, career development, time pressure, individual factors, organizational adjustment, changing global scene, and working under two perceived supervisors. 12,13 The nature of the work of PSE is such that they may not even have spare time to eat well, engage in physical activities, or even go for regular medical checkups. 14,15 PSE who may be prone to CVDs are detected and diagnosed late, hence there is low survival rate most times.…”
mentioning
confidence: 99%